Digging It Up Down Under - Smith, Claire. author. aut Link
XXVI, 325 p.
Keywords: World Archaeological Congress Cultural Hertiage Manual series series editors: Digging it up Down Under by Claire Smith and Heather Burke, Flinders University, Adelaide, SA, Australia What are the secrets to successful archaeology in Australia? What traps are there for the novice archaeologist? How can a hill be a sacred site? Who holds the best repositories of historical documents? What skills and qualities do archaeological consultancy firms look for? What is it that everyone else knows that you don’t? This book contains the answers to these questions, and more. Whether you are a graduate student seeking to gain overseas experience, a volunteer wanting to learn more about archaeology by working on a real site, or a professional archaeologist interested in gaining employment, this volume provides a unique introduction to undertaking archaeology in an Australian setting. Grounded in the social, political and ethical issues that inform Australian archaeology today, Digging it up Down Under includes advice on the local legislative situation, relevant codes of ethics, definitions of artifacts and sites, and the history and characteristic features of the occupation of the continent by both Aboriginal and European people. Professional archaeologists provide their personal tips for working in each state and territory, dealing with a living heritage, working with Aboriginal peoples, and coping with Australian conditions. This book also includes practical advice on finding funding, local practices, getting published, and having fun—all with the aim of making you better equipped to undertake archaeology in the land down under.